DESIGN AND TESTING OF COAXIAL ROTOR DUCTED FAN VTOL UAV - M Kartidjo; S. A Nugroho; R. G Jiniwangun (Mesin, 2009)
In general aircraft are classified into two major categories: fixed wing and rotary wing aircraft which are commonly known as helicopters. The vertical take-off and landing (VTOL) aircraft is designed to be capable of both flying horizontally like a fixed wing airplane and also ascending and descending vertically and thus eliminates the need of a runway [1],[2],[3],[4]. At recently years, Ducted fan VTOL is most popular. The reason behind that fact is the efficiency of power on the maneuver. This paper presents the results of design and testing of coaxial rotor ducted fan VTOL UAV. Pitch and roll moment of this vehicle will controlled with 2 independence control surface that's attached on the bottom of duct. The Ducted profile is applied to the system in order to improve the efficiency thrust at hovering state [3]. The goal of this design is to find optimized rotation speed rotor and distance between rotors. The value of rotation speed and distance between rotors could be simulated in Computational Fluid Dynamics (CFD) Analysis. The target of this simulation is to find some combination minimum yawing moment and maximum thrust at specifics distance between each rotor. In order to validate this simulation and analysis, we used dedicated platform that's could sense thrust and roll, pitch, yaw moment.